Evidence for Contemporary Switching of the O-Antigen Gene Cluster between Shiga Toxin-Producing Escherichia coli Strains Colonizing Cattle - Geue, Lutz; Menge, Christian; Eichhorn, Inga; Semmler, Torsten; Wieler, Lothar H.; Pickard, Derek; Berens, Christian; Barth, Stefanie A. (Frontiers in Microbiology, 2017)
Shiga toxin-producing Escherichia coli (STEC) comprise a group of zoonotic enteric pathogens with ruminants, especially cattle, as the main reservoir. O-antigens are instrumental for host colonization and bacterial niche adaptation. They are highly immunogenic and, therefore, targeted by the adaptive immune system. The O-antigen is one of the most diverse bacterial cell constituents and variation not only exists between different bacterial species, but also between individual isolates/strains within a single species. We recently identified STEC that persistently infecting cattle belonging to the different serotypes O156:H25 (n=21) and O182:H25 (n=15) were of MLST sequence types ST300 or ST688. These STs, differ by a single nucleotide in purA only. Fitness-, virulence-associated genome regions and CRISPR/CAS (clustered regularly interspaced short palindromic repeats/CRISPR associated sequence) arrays of these STEC O156:H25 and O182:H25 isolates were highly similar, and identical genomic integration sites for the stx converting bacteriophages and the core LEE, identical Shiga toxin converting bacteriophage genes for stx1a, identical complete LEE loci, and identical sets of chemotaxis and flagellar genes were identified. In contrast to this genomic similarity, the nucleotide sequences of the O-antigen gene cluster (O-AGC) regions between galF and gnd and very few flanking genes differed fundamentally and were specific for the respective serotype. Sporadic aEPEC O156:H8 isolates (n=5) were isolated in temporal and spatial proximity. While the O-AGC and the corresponding 5’ and 3’ flanking regions of these aEPEC isolates were identical to the respective region in the STEC O156:H25 isolates, the core genome, the virulence associated genome regions and the CRISPR/CAS elements differed profoundly. Our cumulative epidemiological and molecular data suggests a recent switch of the O-AGC between isolates with O156:H8 strains having served as DNA donors. Such O-antigen switches can affect the evaluation of a strain’s pathogenic and virulence potential, suggesting that NGS methods might lead to a more reliable risk assessment.